Common fixed point theorems for generalized G ? ? ? ?? contractive type mappings with applications - Kumar, Manoj Vijaya; Araci, Serkan; Aracı, Serkan (Boletim da Sociedade Paranaense de Matematica, 2019)
Samet et. al. (Nonlinear Anal. 75, 2012, 2154-2165) introduced the concept of α − ψ− contractive type mappings in metric spaces. In 2013, Alghamdi et. al.[2] introduced the concept of G−β−ψ−contractive type mappings in G-metric spaces. Our aim is to introduce new concept of generalized G − η − χ−contractive pair of mappings. Further, we study some fixed point theorems for such mappings in complete G-metric spaces. As an application, we further establish common fixed point theorems for G-metric spaces for cyclic contractive mappings.
Keywords: Common fixed point; Complete G-metric space; Contractive type mapping; Cyclic mappings